Numerical modeling of dam-reservoir interaction seismic response using the Hybrid Frequency–Time Domain (HFTD) method - Sirumbal Zapata, Luis Fernando (2013)
This research work studies the fundamentals of the Hybrid Frequency-Time Domain (HFTD) method for dynamic analysis of structures, applied to the seismic analysis of dam-reservoir interaction systems. The theoretical consistency and accuracy of the HFTD method, based on the frequency domain Fourier analysis, is demonstrated through all the parts of the thesis, but particularly in Chapter 5 for linear and highly non-linear single degree of freedom (SDOF) models subject to several types of loading, and in Chapter 7 for a 2D dam-reservoir interaction finite element model subject to an earthquake ground acceleration loading. On the other hand, a Finite Element Method (FEM) formulation of dam-reservoir interaction problems is presented, being demonstrated the frequency-dependence nature of this type of systems. The fluid compressibility and boundary conditions of the reservoir are analytically identified as the frequency dependent properties of the system. In this context, the HFTD method is proposed as an ideal method for the dynamic analysis of frequency dependent systems with non-linear behavior, being the dam-reservoir interaction problem taken as a case study to prove this hypothesis.